A 3-dimensional prediction model for mechanical strength of basalt-steel fiber-reinforced recycled aggregate concrete based on reaction surface method. (11th October 2021) - Zhang, Chunsheng; Wang, Lei; Zhang, Xianggang; Ding, Yahong
Highlights: The basic mechanical properties of RAC-BS are studied. Fiber volume ratios and blending methods affect the failure modes of RAC-BS. Three mechanical strength trends of RAC-BS were analyzed by the response surface method. The mechanism of mechanical properties revealed by the microscopic view. A 3-D prediction model of RAC-BS intensity with high accuracy was developed. Abstract: The application of fibers being used to Reinforce recycled aggregate concrete (RAC) has received continuous attention in recent years. However, the effect of variation in fiber dose on the basic mechanical properties of RAC has not been carefully distinguished in studies of hybrid fiber reinforced RAC. In the present study, the response surface method was applied to the strength study of the basic mechanical properties of hybrid fiber-reinforced RAC, with emphasis on obtaining the surface morphology of the strength change with fiber incorporation. Microscopic images were applied to detect the changes in surface characteristics of the fragments of fiber-reinforced RAC specimens after stressing, and the mechanism of the basic properties of hybrid fiber-reinforced RAC was revealed in combination with the damage morphology of macroscopic specimens. A three-dimensional prediction model of the mechanical strength of fiber RAC was derived from the surface morphology, and the variation of fiber admixture was extended from a single point to a range, and the effect of two different fiber admixtures on the mechanical strength of RAC was analyzed regionally, which enriched the research method of hybrid fiber-reinforced concrete.